Pilah Sampah dari Sumber: Kunci Utama Pengelolaan Sampah Berkelanjutan di Desa Cimareme Kecamatan Ngamprah - Novawan, Angga; Mardani, Santika Putri; Firmansyah, Dandy; Puja, Dewi; Rahmawati, Novie; Ghassani, Aldyth; Sugiharto, Dede Lucky; Muhamad Dias, Muhamad Dias; Devi, Santi; Jatiningtyas, Noor Aini; Ramadhiyani, Tyesha; Huda, Khairul; Sani, Sani; Nh. Salsabiela; Rahmanda, Rizky; Maulana, Adithiajaya; Tjahjadinata, Ruddy; Kusnadi; Romy, Achmad; Rohayati, Ati Sandi; Safira, Resi; Febriana, Esra; Ramadhan, Gilang; Pratama, Riqfi Aditya; Mardiansyah, Andri (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
The Community Service Program (PKM) was implemented in RW 05, Cimareme Village, Ngamprah District, West Bandung, with a focus on waste management and community empowerment. This area has economic, social, and educational potential that can be developed through a cross-disciplinary approach. The main activities include counseling, waste management, campus promotion, and participation in community social activities. The peak of the activity in the form of a Final Workshop emphasized the increase in environmental awareness, active community participation, and positive relations between students and the community. This PKM is expected to be the first step in sustainable collaboration between universities and partner villages.